Stoichiometric N:P Ratios, Temperature, and Iron Impact Carbon and Nitrogen Uptake by Ross Sea Microbial Communities. Issue 9 (19th September 2018) - Spackeen, Jenna L.; Bronk, Deborah A.; Sipler, Rachel E.; Bertrand, Erin M.; Hutchins, David A.; Allen, Andrew E.
Abstract: Phytoplankton growth in the seasonally productive Southern Ocean is typically limited by iron (Fe). In the next century, however, Fe inputs and temperature are predicted to increase. Dissolved concentrations of nitrogen (N) and phosphorus (P) may also change due to physical and biological drivers, altering the stoichiometric N:P ratio of the water column. Two separate experiments were conducted to study how these predicted changes will impact nutrient utilization by two natural microbial communities from the Ross Sea, Antarctica. The first investigation focused on a Terra Nova Bay community amended with Fe and grown under a wide range of seven different N:P ratios. Building on the results of the first study, a McMurdo Sound community was incubated under a factorial design at high, medium (ambient), and low N:P ratios, with and without Fe addition, and at ambient versus elevated temperature. In both experiments absolute uptake rates of bicarbonate, nitrate, and amino acids by two size fractions (0.7–5.0 μm and > 5.0 μm) of microorganisms were measured using stable isotopes. For Terra Nova Bay microorganisms, significant differences in nutrient uptake rates occurred when the N:P ratio was elevated, and nitrate uptake rates significantly increased early in the experiment but were not different at the end. For McMurdo Sound microorganisms, changing the N:P supply ratio did not have a clear effect, while temperature elevation and/or Fe addition significantly increased nutrient uptake. Results indicate that changing the dissolved N:P ratio can potentially alter nutrient uptake rates; however, the impact of temperature and Fe are greater. Plain Language Summary: The Southern Ocean is one of the most biologically important ecosystems on our planet. Microscopic plants, called phytoplankton, form the base of the food web in the Southern Ocean and play a direct role in regulating how much and how fast elements like nitrogen and carbon are cycled throughout the world ocean. The goal of this research was to determine how predicted changes in the environment will impact how fast phytoplankton use these elements. The conditions that we tested included elevated temperature, addition of iron, and the proportion of nitrogen to phosphorus in the seawater. These parameters were selected because temperatures are increasing in the Southern Ocean, and the relative availability of nutrients can alter what species of phytoplankton are present and how fast they grow. Phytoplankton were collected from two locations in the Ross Sea, Antarctica, and grown for a few weeks under experimental conditions. Our results demonstrate that all three parameters, warmer temperatures, the addition of iron, and changing nitrogen to phosphorus ratios will increase how fast phytoplankton use nitrogen and carbon, but the impact of elevated temperature and the addition of iron had a much larger impact than the nitrogen to phosphorus ratio. Key Points: Responses of Ross Sea microorganisms to changing dissolved N:P ratios, temperature, and Fe vary seasonally and among taxa Increasing the N:P ratio of the seawater increased nitrate uptake rates, but only over short time scales and during the late‐season bloom Temperature elevation and Fe addition are more significant drivers of change than N:P supply ratios when Phaeocystis is dominant